Clinical Guidelines of the Russian Society of Surgeons, the Russian Gastroenterological Association, the Association of Surgeons-Hepatologists and the Endoscopic Society “REndO” on Diagnostics and Treatment of Chronic Pancreatitis - V. T. Ivashkin; A. G. Kriger; A. V. Okhlobystin; M. A. Anischenko; S. S. Kardasheva; S. A. Alekseenko; S. F. Bagnenko; M. I. Bykov; S. A. Budzinskiy; I. M. Buriev; V. A. Vishnevskiy; E. I. Galperin; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present modern methods of diagnosis and treatment of chronic pancreatitis for gastroenterologists, general practitioners and physicians.Chronic pancreatitis (CP) is a long-term inflammatory disease of the pancreas, manifested by irreversible morphological changes in the parenchyma and pancreatic ducts, which cause pain and/or persistent impairment of function. Current concept on the etiology of CP is reflected by the TIGAR-O classification. The criteria for establishing the diagnosis of CP include typical attacks of abdominal pain and/or clinical and laboratory signs of exocrine, endocrine insufficiency with the mandatory detection of characteristic morphological changes (calcifications in the parenchyma and pancreatic ductal stones, dilatation of the main pancreatic duct and its branches). CT, MRCP, and pancreatobiliary endosonography are recommended as the methods of choice to verify the diagnosis of CP. Conservative treatment of patients with CP is provided for symptom relief and prevention of complications. Individual cases with severe non-interactable abdominal pain, as well as a complicated course of the disease (development of ductal hypertension due to main pancreatic duct stones or strictures, obstructive jaundice caused by compression of the common bile duct, symptomatic postnecrotic cysts, portal hypertension due to compression of the portal vein or thrombosis of the splenic vein, persistent duodenal obstruction, pseudoaneurysm of the celiac trunk basin and the superior mesenteric artery) serve as an indication for endoscopic or surgical treatment. The Guidelines set out modern approaches to the diagnosis, conservative, endoscopic and surgical treatment of CP, and the prevention of its complications.Conclusion. The implementation of clinical guidelines can contribute to the timely diagnosis and improve the quality of medical care for patients with chronic pancreatitis.